Some actual aspects of struggle against on terrorism within the framework of the anti-crime activities of the SCO. (Journal of actual problems of jurisprudence, 2016)
The author of the article stresses the urgency of the fight against terrorism by increasing the scale of its social danger and geographic expansion. Analyzing the contractual base of the SCO, regulating the joint efforts of the member states to detect and prevent terrorism and related acts, the authors draw attention to gaps in legal regulation. As a solution of this problem it is offered within the Convention on Combating Terrorism, Separatism and Extremism in 2001 to provide rules for the root causes of terrorist activity. It is based on the fact that the introduction of such supplement can improve and increase the effectiveness of the Convention in this sphere.
Keywords: fight against terrorism; the Shanghai Cooperation Organization; the Convention on Combating Terrorism; Separatism and Extremism; the Regional Anti-Terrorist Structure of the SCO